Barriers Confronting Nurses' Practices during Intravenous Cannulation for Children in the Emergency Units - Kadhim Jawad Kadhim, Serwan Jafar Bakey, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: children admitted to hospitals, especially to emergency departments, always need intravenous catheterization to receive treatment. It is still hard for healthcare providers, including nurses to perform intravenous catheterization (cannulation) for pediatric patients. Barriers to perform intravenous cannulation for pediatric patients should be determined to enhance nurses’ practices and performance to achieve this action and decrease patients’ suffering. Aims of the study: This study aimed to assess nurses’ practices and barriers confronting nurses during Intravenous Cannulation among Pediatric Patients, and to find out relationships between nurses’ practices and their demographic characteristics that include age, gender, level of education, years of experience in nursing, years of working, training sessions Methodology: A descriptive study design was conducted on Emergency nurses at al-Hussein teaching hospital for the period of October 15th, 2021, to March 30th, 2022. A non-probability (Purposive) sample was selected of 25 nurses who work at al-Hussein teaching hospital. The data was collected using a previously prepared questionnaire and official agreement to use the study questionnaire was obtained from the original author. Descriptive statistics (frequencies, percentages, mean, and standard deviation) and inferential statistics (contingency coefficient) were used in the data analysis. Results: Results presented that nurses were confronting barriers about documentation of intravenous cannulation and procedures of removing intravenous cannula. Moreover, results showed a significant relationship between nurses’ practices with intravenous cannulation with their gender at p value = .031. Conclusion: The study concluded that nurses face barriers with pediatric intravenous cannulation especially with the use of right procedure to remove the cannula.